Reading with Methodological Perspective Bias: - Richard Deady (Grounded Theory Review: An International Journal)
The following is a naïve narrative of my journey into classic grounded theory (CGT) and the consideration of the possible existence of methodological perspective bias when reviewing literature. Whilst research bias has been viewed from a number of differing perspectives, such as sample bias, interviewer bias, publication bias etc (Sica, 2006), there appears a dearth of discussion within the literature on methodological perspective bias, as well as, a reluctance to publicly acknowledge the existence of such bias. For the purpose of this paper the concept of bias is defined as “a source of systematic error … deriving from a conscious or unconscious tendency on the part of a researcher to produce data, and/or to interpret them, in a way that leans towards erroneous conclusions which are in line with his or her commitments” (Hammersley and Gomm, 1997, p.1).